Immunological interactions of Chilo suppressalis Walker (Lepidoptera: Crambidae) with the native entomopathogenic fungi. (May 2021) - Shahriari, Morteza; Zibaee, Arash; Khodaparast, Seyyed Akbar; Fazeli-Dinan, Mahmoud; Hoda, Hassan; Armand, Alireza
Abstract: Entomopathogenic fungi can attack many insect hosts and have been applied as the eco-friendly alternatives to synthetic chemicals for the control of pests. Insects have developed different defense systems encountering entomopathogens including humoral and cellular immune responses. In the present study, injection of some native entomopathogenic fungi to the Chilo suppressalis Walker larvae resulted in an enhancement of the cellular and antimicrobial defenses. The numbers of total and differential hemocytes increased rapidly in the first 3 and 6 h but those gradually reduced 12 and 24 h post-injections. The nodule formation and phenoloxidase activity increased at the time intervals after fungal infection. A similar trend was found in the transcription of antimicrobial peptides including attacin1 and 2, cecropin1 and 2, gallerimycin, defensin, lysozyme, and prophenoloxidase-activating proteinase-3 during infection fungi. In all cases, the target gene transcription was upper in the larvae injected by the fungi than that of control larvae. These results may elucidate better knowledge on the interaction of the fungi present in agroecosystems with the target insect pest. Graphical abstract: Image 1 Highlights: The entomopathogenic fungi increased the number of hemocytes in Chilo suppressalis after 3 and 6 h. The nodule formation and phenoloxidase activity increased at the same time intervals. The EF injection upregulated the expression of some antimicrobial peptide genes.